PEMBINAAN NILAI-NILAI PENDIDIKAN MULTIKULTURAL DI SDN 54 ANAK AIR, PADANG - Desi Fitria; Sri Wahyuni (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2021)
This study describes how to foster multicultural education values ​​at SDN 54 Anak Air. The type of research used is qualitative research with a descriptive approach. Research data were collected through observation, interviews and documentation studies. Data analysis was carried out by reducing data, presenting data and drawing conclusions. Test the validity of the data is done by triangulation of data sources. The research findings show that the interaction of students from different cultures in grades one, two and three tends to be awkward and closed. Meanwhile, the interaction at the further grade level is very intimate and tends to be open. The interaction of students with students from different cultures has shown an appreciation for cultural differences. So that in the interaction the values ​​of multicultural education have been built, namely the value of tolerance and the value of equality. The interaction of teachers with students of different cultures shows the development of the values ​​of multicultural education, namely the value of tolerance, democracy, the value of equality and the value of justice. Activities held at SDN 54 Anak Air both in-class and out-of-class activities at SDN 54 Anak Air have included the values ​​of multicultural education. The understanding of the teachers at SDN 54 Anak Air towards multicultural education is theoretically still lacking, however in their actions and treating students of different cultures it contains the values of multicultural education.